Comparison of Bone Mineral Density of Dominant and Non-dominant Forearm of Badminton Players - Mustafa Şakir Akgül; Arzu Altunel; Veli Volkan Gürses; Bilgehan Baydil (Selcuk University, 2019)
ABSTRACTResearch related to arm bone density of badminton players focused mainly on humerus, how much forearm exposed to physical load is affected by this stress has been studies less. Thus, the aim of this study was to investigate mineral density of dominant and non-dominant forearm bone mineral density of badminton players who have been regularly playing badminton for 10 years. 12 male badminton players whose dominant arms were the same voluntarily participated in this study. Bone Mineral Density (BMD) of the players was evaluated with Dual X Ray Absorptiometry (DEXA). Data was evaluated with SPSS 23. Controlled research method was used to estimate BMD of the players. Differences between dominant and non-dominant arms were assessed with a non-parametric test, Wilcoxon Signed Rank Test. P value was set at p lt;0.05. Significant difference was found between BMD of dominant right ultra-distal part and BMD of non-dominant left ultra-distal part (z:-2,94, sig:0,00) and between BMD of dominant right proximal part and BMD of  non-dominant left proximal part (z:-2,09, sig:0,03). There was no significant difference between dominant proximal 1/3 part and non-dominant proximal 1/3 part (z:1,85, sig:0,06). As a result, long-term badminton training has positive effects on BMD.